Efektivitas penambahan hormon auksin (IBA) dan sitokinin (BAP) terhadap sambung pucuk Alpukat (Persea americana mill.) - Pramudito Pramudito; Karno Karno; Eny Fuskhah (Journal of Agro Complex, 2018)
The purpose of this research was to study the effect of hormone Auxin (IBA) and sitokinin (BAP) and the most effective concentration in graftingof avocado variety mentega. The experiment used completely randomized factorial design. The first factor was various concentrations of IBA (0, 100, and 200 ppm) and the second factor was various concentrations of BAP (0, 100, and 200 ppm). Each treatment was repeated five times. Parameters were time of shoots emergence, shoot length, diameter shoot diameter, and the number of leaves. The data were subjected to analysisof variance and continued by DMRT (Duncan Multiple Range Test). The result showed that the level of IBA concentration gave significant effect (P<0,05) to time of shoot emergence, shoot length, shoot diameter, and the number of leaves. Level of BAP concentrations gavesignificant effect (P<0,05) to number of leaves. There was no interaction between type of auxin and concentration on grafting of avocado variety mentega. Keywords : Avocado, Persea americana, wedge grafting, IBA, BAP.